Mauri Ora: Creating a model of practice using Indigenous Tikanga. - Waru, Sheryl; Popata, Desrae (Te Kaharoa, 2021)
As an Adult Educator, combined creative thinking and critical thinking can often provide learners with the tools to be innovative through their practices. He Pūawai is an Adult Tertiary Teaching L5 program at Te Wānanga o Aotearoa. The course is a 20-week program comprised of four learning modules providing skills and learning tools for facilitators, tutors or trainers teaching Adults. I have collaborated with a tauira to extend a Kaiako perspective and tauira vision that created a model of practice and framework. The tauira were the Semester A He Pūawai program. This framework applies Ngā Takepū, Ahurutanga, Kaitiakitanga, Koha and Mauri Ora, and these principles are embedded in Adult Teaching through the delivery and learning practices at Te Wānanga o Aotearoa. Takepū is about caring for people, relationships and cultures through a holistic approach in an educational context for all learners (Pohatu & Timata, 2008). I will discuss how ‘Mauri’ informed and balanced innovation and creative skills that enhance relationship building. Pohatu & Pohatu (2011) refer to ‘Mauri’ as the formation of human relationships. Mauri emphasises the “how and why” we shape how we learn, teach and behave (p. 1).